2017
DOI: 10.15244/pjoes/67553
|View full text |Cite
|
Sign up to set email alerts
|

Delinking Indicators on Transport Output and Carbon Emissions in Xinjiang, China

Abstract: This paper identifies the driving forces of CO 2 emissions from 1990 to 2014 in Xinjiang's transport sector based on the logarithmic mean divisia index (LMDI) method. Then we introduce the decoupling index to further quantitatively analyze the delinking indicators on the transport sector's growth and environmental pressures. The results indicate that: 1) CO 2 emissions increased significantly with an average annual growth rate of 8.7%. On the contrary, energy intensity has declined constantly over the study pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The paper endeavors to determine the decomposition of driving factors that affect the relationship between Bangladesh's transport sector development and CO 2 emissions due to energy consumption from the year 1990 to 2017 using the Logarithmic-Mean Divisia Index (LMDI for Bangladesh, [28] for the Eurasian corridor (29 countries). On the other hand, the scope of these studies is China from the regional perspective [29][30][31][32][33][34][35][36][37]. Most studies have covered several provinces.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%
“…The paper endeavors to determine the decomposition of driving factors that affect the relationship between Bangladesh's transport sector development and CO 2 emissions due to energy consumption from the year 1990 to 2017 using the Logarithmic-Mean Divisia Index (LMDI for Bangladesh, [28] for the Eurasian corridor (29 countries). On the other hand, the scope of these studies is China from the regional perspective [29][30][31][32][33][34][35][36][37]. Most studies have covered several provinces.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%
“…They figured out that economic growth is the main factor responsible for CO 2 emission growth of the modes considered in their analysis. Dong et al (2017) combined the decoupling index together with the LMDI method to identify the driving forces of CO 2 emissions in the Xinjiang transport sector for the period 1990-2014. They showed that economic growth, the size of the population and the energy mix contributed to the rise in CO 2 emissions.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Sustainable transport systems, both passenger and freight, should be economically and technically feasible, but also low-carbon or ecologically acceptable. The calculation of the greenhouse gas emissions in transport projects is becoming the primary goal of transport companies as part of an effort to implement national and global strategies to reduce carbon emissions, reduce energy demand and reduce negative environmental impacts [8][9]. In order to meet these challenges, all modes of transport have to be improved in terms of energy efficiency [10].…”
Section: Introductionmentioning
confidence: 99%